CHINA’S INFLUENCE ON AUSTRALIA'S POSITION IN THE SOUTH PACIFIC IN THE SECURITY SECTOR AND DEVELOPING SECTOR - Ramadhani, Suci Nur; Noer, Mohammad (Universitas Nasional, 2022)
After the economic growth, the government system, and security in the Solomon Islands have started to improve. China is here to increase its influence in the Region. China's presence in the Solomon Islands puts Australia's position at risk. The research entitled